High-affinity interleukin 2 binding by an oncogenic hybrid interleukin 2-epidermal growth factor receptor molecule. - Bernard, O (1987)
Both interleukin 2 (IL-2) and epidermal growth factor (EGF) receptors exist in two forms that differ with respect to affinity for their ligand. Only the high-affinity receptors appear to be responsible for the proliferation signal delivered upon binding of the growth factor. Fibroblasts transfected with IL-2 receptor cDNA generate only low-affinity receptors for IL-2, but fusion of membranes from these fibroblasts with T-cell membranes converts some receptors to high affinity, indicating the involvement of a T cell-specific factor in the generation of high-affinity receptors. We have constructed a chimeric cDNA molecule containing the extracellular IL-2-binding domain of the IL-2 receptor cDNA and the transmembrane and intracellular tyrosine kinase domains of the EGF receptor cDNA. When transfected into fibroblasts, this IL-2-EGF receptor cDNA generated high-affinity receptors for IL-2. Moreover, fibroblasts transfected with the chimeric molecule were morphologically transformed and produced rapidly growing tumors in nude mice.